1986
DOI: 10.1007/bf02128138
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the peripheral vasculature of various organs in patients with sarcoidosis—Possible role of microangiopathy

Abstract: Vascular involvement in sarcoidosis is briefly reviewed with emphasis on the outcome of a 10-year project-study by the Sarcoidosis Research Committee of the Japanese Ministry of Health and Welfare. Examples of vascular disorder associated with sarcoidosis are presented, including basal lamina layering of the capillaries in the skeletal muscle, cardiac muscle, and lung, glomerulopathy in the kidney, vascular changes in the ocular fundus and bronchi, and impaired peripheral circulation that could be detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…Because of its severity, the thickening differs clearly from that in other cardiomyo pathies. Thickening, either with or without multilayering, has been reported to occur in the basement membranes of myocardial cap illaries in diabetes mellitus [37], myocardial sarcoidosis [38,39] and myxedema [40], and in mice with a genetically transmitted cardio myopathy that is associated with diabetes mellitus (KK mice) [41], In all of these in stances, the affected basement membranes of ten tend to form multiple, concentrically ar ranged layers, which may be individually somewhat thicker than a single normal base ment membrane; however, thickening of basement membranes consisting of a single layer of material also occurs in diabetes melli tus and myxedema [37. 40], None of our patients had these diseases.…”
Section: Basement Membrane Thickeningmentioning
confidence: 99%
“…Because of its severity, the thickening differs clearly from that in other cardiomyo pathies. Thickening, either with or without multilayering, has been reported to occur in the basement membranes of myocardial cap illaries in diabetes mellitus [37], myocardial sarcoidosis [38,39] and myxedema [40], and in mice with a genetically transmitted cardio myopathy that is associated with diabetes mellitus (KK mice) [41], In all of these in stances, the affected basement membranes of ten tend to form multiple, concentrically ar ranged layers, which may be individually somewhat thicker than a single normal base ment membrane; however, thickening of basement membranes consisting of a single layer of material also occurs in diabetes melli tus and myxedema [37. 40], None of our patients had these diseases.…”
Section: Basement Membrane Thickeningmentioning
confidence: 99%
“…Vracko reported that BLL was frequently observed in the skeletal muscle of patients with diabetes mellitus [6]. Mikami et al found BLL in the myocardium as well as skeletal muscle in patients with sarcoidosis [7]. Few studies have described BLL in the heart muscle of DCM [8].…”
Section: Discussionmentioning
confidence: 99%
“…30) It was reported by Mikami, et al that the electron microscopic study disclosed basal lamina layering (BLL) of the capillaries in the skeletal muscle of sarcoidosis patients. 31) Sekiguchi, et al found BLL in EMB specimens from 77.8% of patients with sarcoidosis. 28) They concluded that sarcoidosis with microangiopathic processes could exist and these were an important element of the disease.…”
Section: Sarcoidosismentioning
confidence: 99%